Minimally Invasive Techniques in Colorectal Surgery: A paradigm Shift Towards Better Outcomes and Faster Recovery - Sattar, Sabah; Shaikh , Adeel Ahmed; Ayoub , Jahangir; Fahad, Shah; Das, Manghan; Javaid, Rimsha (Indus Journal of Bioscience Research, 2025)
This study compared and analyzed clinical outcomes of minimally invasive colorectal surgery to open surgery, particularly looking at complications after surgery, time spent in the hospital and which factors impact recovery. From selected tertiary hospitals known for colorectal surgery, we gathered 200 patient records for this study using convenience sampling. Several statistical approaches such as t-tests, chi-square independence tests and linear regression, were applied to study how surgery methods and the results achieved by patients are related. On average, those given minimally invasive surgery was in the hospital for 5.3 days, far less than the 8.5 days for those receiving open surgery (p < 0.001). Also, chi-square analysis found that the method of surgery was significantly related to postoperative complications, with minimally invasive surgery leading to fewer problems than open surgery (p < 0.001). Another finding is that the kind of surgery, a patient’s age and the level of additional health problems affect the length of stay and gender did not have an impact. Even when considering other factors, minimally invasive surgery was connected with a 3.2 day decrease in the hospital stay duration. All of these studies show that patients who have minimally invasive colorectal surgery enjoy quicker recoveries, lower chances of complications and shorter time in the hospital. Strong evidence drives the introduction and adoption of minimally invasive surgery methods in daily colorectal surgery to improve health results and health service efficiency.